Edukasi Pencegahan Kekerasan pada Remaja di SMAN 5 Padang - Anggela Pradiva Putri; Arinil Haq; Melisa Yenti (Warta Pengabdian Andalas, 2023)
Violence is an act that refers to an attitude or behaviour that is inhumane so that it can hurt other people. People who commit violence not only harm their victims but will also make the perpetrators get punished according to applicable law. Data on youth violence compiled by the Ministry of Women's Empowerment and Child Protection (KPPA) in 2016 shows that Indonesia still has problems with youth and child violence. The activity was disseminated to partners, namely SMAN 5 Padang, which, although no cases have been reported, there has never been socialization and education about violence in adolescents. There was a concern and request for the school as a partner to socialize. The number of cases of violence, such as bullying and brawls, is something that we need to pay attention to. This service activity aimed to provide education and prevention regarding violence in adolescents. Activities were carried out in the form of educational activities as well as pre-tests and post-tests to measure students' knowledge of youth violence. Questions were sourced from socialization material obtained from various references. The pre-test results found that more than half of the students (73%) had good knowledge about violence in adolescents, and the post-test showed an increase in knowledge of 100%. It was hoped that with this activity, students could be more aware of all forms of violence around them, and the school could routinely provide continuing education on preventing youth violence.